Urgensi Kegiatan Keagamaan Dalam Menjaga Kestabilan Iman Pada Generasi Z - Rifqi, Muhammad Sulthon; Mushaffa, Arju; Sa'adah, Azka Alfi Nurus; Sholikhah, Mar’atus; Fasya, Zaini (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This paper discusses the urgency of religious activities in maintaining the stability of faith in generation Z. This research uses literature study type research, with a descriptive approach. Seeing today's generation Z who lack spiritual understanding of aqidah (faith), which causes their thinking and behavior to experience a lot of mistakes, with this, the urgency of religious activities is very important to follow and implement into the lives of generation Z, with the hope of providing understanding and maintaining the quality of their aqidah (faith), so that their behavior and faith remain stable and away from understanding and bad associations. Religious activities, such as digital studies, religious concerts, religious organizations, which have recently attracted a lot of young people, especially generation Z because these activities are fun because the methods and approaches carried out are specific to today's generation which has digital characteristics. With these activities, in fact, it is also very effective in increasing understanding and increasing their spiritual faith.